2018
DOI: 10.1186/s13028-018-0372-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation in dogs with advanced-stage heart failure

Abstract: BackgroundAlthough human studies have shown that inflammation plays a role in the development of congestive heart failure, scarce information exists on white blood cell count (WBC) and differential cell counts in various stages of heart failure in man and dogs. A few studies demonstrated increased concentrations of C-reactive protein (CRP), a major acute-phase protein, in cardiac diseases in dogs. Our research aimed to investigate whether CRP concentration, WBC and neutrophil count (NEUT), as markers of system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 50 publications
3
30
3
Order By: Relevance
“…The most commonly studied APP in heart failure is CRP. In dogs, CRP has been shown to be increased in CHF and correlated with disease severity 33,36,38 . It does not appear to be a major APP in cats, 64 but interestingly, we identified significant positive correlations of CRP with renal markers.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The most commonly studied APP in heart failure is CRP. In dogs, CRP has been shown to be increased in CHF and correlated with disease severity 33,36,38 . It does not appear to be a major APP in cats, 64 but interestingly, we identified significant positive correlations of CRP with renal markers.…”
Section: Discussionmentioning
confidence: 57%
“…So far, only a few studies have investigated APPs in cats with cardiac disease 26,29,30 . In humans and dogs, several APPs have been associated with heart failure 31‐38 . The relationship between APPs and CHF in cats, however, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is associated with several limitations. First, the sample size was small and dogs were not sub-divided as MMVD and DCM in this study as has been in a previous study about this topic in which it was indicated that etiology had no effect on the results of hematology, serum CRP and echocardiographic measurements (13). Therefore, this should be considered a pilot study and additional studies should be made in a larger population and also with different speci c diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although both of them are commonly considered non-in ammatory conditions (6,7), studies have found increased circulating in ammatory cytokines in dogs and humans with CHF due to MMVD (8,9) and DCM (7,10). Increased expression and release of in ammatory cytokines such as tumour necrosis factor (TNF-α), as well as serum C-reactive protein (CRP), have been described in humans (11,12) and dogs with CHF (13). Increased levels of monocyte chemoattractant protein 1 (MCP-1) and decreased levels of interleukins have also been found in dogs with CHF (8), but there is no data available on how CRP or other in ammatory biomarkers can change in severe cases (6).…”
Section: Introductionmentioning
confidence: 99%
“…In ammatory and oxidative stress markers can contribute to cardiac remodeling in the progression of CHF in dogs. In this study, CHF due to MMVD or DCM was diagnosed based on a thorough cardiopulmonary assessment as reported in the previous studies (5,13), and classi ed by stage A through D according to the ACVIM consensus statement guidelines (3).…”
Section: Discussionmentioning
confidence: 99%